2016
DOI: 10.1257/app.20150023
|View full text |Cite
|
Sign up to set email alerts
|

The Returns to Microenterprise Support among the Ultrapoor: A Field Experiment in Postwar Uganda

Abstract: We show that extremely poor, war-affected women in northern Uganda have high returns to a package of $150 cash, five days of business skills training, and ongoing supervision. Sixteen months after grants, participants doubled their microenterprise ownership and incomes, mainly from petty trading. We also show these ultrapoor have too little social capital, but that group bonds, informal insurance, and cooperative activities could be induced and had positive returns. When the control group received cash and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 37 publications
6
80
1
Order By: Relevance
“…Of course, our results should not be taken as evidence that credit constraints never generate poverty traps. Recent studies by Blattman, Fiala, and Martinez (2014) and Blattman et al (2016) suggest that credit constraints may well be preventing latent entrepreneurs from launching successful businesses in recently conflict-affected regions of northern Uganda. However, our findings resonate with a number of recent studies of cash grants and other credit market interventions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, our results should not be taken as evidence that credit constraints never generate poverty traps. Recent studies by Blattman, Fiala, and Martinez (2014) and Blattman et al (2016) suggest that credit constraints may well be preventing latent entrepreneurs from launching successful businesses in recently conflict-affected regions of northern Uganda. However, our findings resonate with a number of recent studies of cash grants and other credit market interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Economic theory suggests that such interventions can help potential entrepreneurs who have limited opportunities to save or borrow to start or expand profitable businesses, and one recent study suggests that cash grants can help unemployed youth launch businesses and increase their incomes (Blattman, Fiala, and Martinez 2014). However, a growing body of evidence on the the returns to capital among entrepreneurs suggests that credit constraints may not be the main obstacle limiting the growth of female-owned microenterprises: evaluations to date have found that, in most cases, cash grants to female entrepreneurs do not lead to sustained increases in business profits or income (De Mel, McKenzie, and Woodruff 2008, De Mel, McKenzie, and Woodruff 2009, Fafchamps, McKenzie, Quinn, and Woodruff 2011, Fiala 2014, Karlan, Knight, and Udry 2015, Blattman et al 2016. 1 Taken together, these results suggest that many women who operate small businesses are "subsistence entrepreneurs" (Schoar 2010) who lack either the ability or the inclination to expand their enterprises; if this is true, access to capital (alone) is unlikely to have major impacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supervisions and training have shown positive impacts on business survivals. Provisions of insurances and development of group bonding have enhanced microenterprise outcomes (Blattman, Green, Jamison, Lehmann, & Annan, 2016). Both financial intermediation and BDS have widely impacted enterprise development in SHG-based microfinance programs (e.g., see Hyman & Dearden, 1998;Maes & Basu, 2005;Panda, 2016a).…”
Section: Entrepreneurial Orientation and Intermediationmentioning
confidence: 99%
“…There also exist randomized evaluations that are similar in spirit to graduation programs but not labeled as such and not included in the review (see e.g. Blattman et al, 2016). Overall, the rates of cost-effectiveness in Banerjee et al (2015) appear representative of the available body of evidence, though a forward-looking interpretation of the expected cost-effectiveness of similar programs might consider adjusting these rates downward to account for the possibility of implementation failure.…”
mentioning
confidence: 99%